Adequacy of empirical antibiotic for patient admitted to ICU with sepsis - Hashim, Halimatul Nadia M (2016)
Objectives: Sepsis is one of the commonest causes of ICU which lead to high mortality and morbidity. Early empirical antibiotic treatment is important to improve the patient's outcome . The aim of this study was to assess the adequacy of empirical antibiotic therapy for sepsis patients in Intensive Care Unit (ICU), Hospital Sultanah Nur Zahirah (HSNZ), Kuala Terengganu. Methods: This was a retrospective, observational study to evaluate the adequacy of empirical antibiotic given to patients who were diagnosed with sepsis in ICU. 130 cases who were admitted to ICU for sepsis from January 2013 to December 2013 were selected and their medical record were traced from HIS (Hospital Information System) and reviewed. Their demographic profiles, underlying comorbidities, antibiotic usage, culture and sensitivity results as well as patient’s outcome were reviewed. The adequacy of empirical treatment in each case was determined. Adequate empirical antibiotic treatment was considered adequate if spectrum, dose, application modus, and duration of therapy were appropriate according to MSIC (Malaysian Society of Intensive Care) guidelines. Results: Among 130 intensive care unit patients with sepsis, 119 (91.5%) received adequate antimicrobial treatment. In this group, the mean age of patients was 51.8 year old and 51.3% of them were men.112 (86.2%) patients presented with septic shock and 104 (87.4%) of them were given adequate empirical antibiotic. The main sources of bacteremia in this group were from lungs (42%), abdomen (21%) or skin and soft tissue (15.1%). The microorganisms most frequently isolated were Escherichia coli 13 (37.1%), Burkholderia pseudomallei 7 (20.0%), followed with Klebsiella pneumonia 6 (17.1%), Acinobacter baumanii 4 (11.4%) and Leptospira interrogan 2 (5.7%). For patients with gram positive culture, which affected 25 patients with adequate treatment, coagulase negative staphylococcus, 11 (44.0%), and staphylococcus aureus, 11 (44.0%), were the most common organisms. This was followed with streptococcus pneumonia in 3 (12.0%) patients. Among the adequate group of patients, cephalosporin was the most frequently used, 63 (52.9%), carbapenem in 21 (17.6%) patients became the second option followed with Piperacillin/tazobactam in 17 (14.3%) patients and Amoxycillin / clavulanic acid 6 (5.0%). Comparing both group of patients who received adequate and inadequate empirical antibiotics therapy, the outcome were not statistically significant in terms of the duration of ventilation and ICU stay, duration of hospitalization as well as patient mortality and survival. However there was 10% reduction of mortality in adequate treatment group